PRE-SERVICE EFL TEACHERS’ COGNITION OF ENGLISH TEXTBOOKS IN VOCATIONAL SCHOOLS - Angga Maulana; Siska Rizkiani (STKIP Siliwangi, 2019)
Teacher cognition may define teachers’ professionalism. It refers to the teachers’ ability of knowing, believing, and thinking about teaching. This study is trying to look at the pre-service English teachers’ cognition on English textbook of vocational schools in order to raise the quality of pre-service English teacher and benefit the foundation of thinking abilities and teaching reflection on the textbook usage in their classroom. It is widely known that textbooks are one of the important aspects in the teaching-learning process. This research used descriptive method. The participant of this study were three pre-service English teachers who has passed the teaching training program. They used to be assigned to do their teaching training at different vocational schools. Each school applied different English textbook. Descriptive analysis employed to obtain a picture of pre-service English teacher cognition on English textbooks after distributing the questionnaire and administering interview. The results showed that all the participants believe that there is no specific material in English textbooks to any particular major or department of vocational school. It was also found that the textbooks do not meet and train students' four language skills in balance. This made them to create or add related materials from various sources.Keywords: English Textbook, Pre-service EFL Teacher, Teacher Cognition